(untitled) (Indonesian Economic Justice Review, 2024)
This paper explores the role of the Indonesian government in promoting economic justice through wealth distribution policies, assessing the effectiveness of government programs aimed at reducing economic inequality. Indonesia’s rapid economic growth over the past few decades has been accompanied by rising wealth disparities, with the richest segment of society continuing to capture a disproportionate share of the national income. The study critically evaluates the role of key policies such as progressive taxation, social welfare programs, and public spending on education and healthcare in addressing wealth inequality. It also examines the impact of wealth distribution on social mobility, poverty reduction, and the broader goal of achieving inclusive growth. Using a combination of quantitative data from national economic reports and qualitative insights from local communities, the paper assesses the challenges the government faces in balancing growth with equity. The findings suggest that while Indonesia has made strides in poverty reduction, its wealth distribution remains highly uneven, with marginalized groups—particularly rural populations and ethnic minorities—facing continued economic exclusion. The paper concludes with policy recommendations aimed at improving wealth distribution, including a more progressive taxation system, the expansion of social safety nets, and greater investments in rural development and education.